Truss layout design and optimization using a generative synthesis approach. (15th January 2016) - Hooshmand, Amir; Campbell, Matthew I.
Highlights: The approach uses load flow principal for automating the design of cable trusses. Grammar rules use this domain knowledge to quickly find optimal solutions. Approach and results handle problems with multiple loads and supports. Approach and results address 2D and 3D test problems without increase in the time. Tree-search algorithm explores design space of many topologies. Abstract: This paper describes a generative methodology for optimum design of truss structures. The novelty of the proposed method is its combination of generative design synthesis methods with conventional gradient-based optimization and simulation models. This combination is able to achieve optimal topologies and shapes for cable trusses under various constraints: stress, displacement, stability. Furthermore, manufacturing issues properly limit the generated solutions. A graph grammar is used to define different topologies for a given load problem. The effectiveness of the method is checked by solving a variety of available test problems found in the literature as well as several new three-dimensional solutions.